A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence - Hrivniak, Ľuboš; Sroka, Pavel; Turkmen, Gencer; Godunk, Roman J.; Kazanci, Nilgun (Magnolia Press, 2019)
Epeorus (Caucasiron) turcicus sp. nov. is described based on larvae from NE Turkey. The new species can be distinguished from other Caucasiron by a unique combination of several diagnostic characters: the presence of a rounded hypodermal medial femur spot, colouration of abdominal terga and sterna, narrow gill plate VII, fine hair-like setae on the surface of abdominal terga, and absence of postero-lateral projections on tergum X. In addition to morphological analysis, two single-locus analytical approaches are employed for delimiting the new species using COI sequences (Automatic Bar-code Gap Discovery, ABGD; and General Mixed Yule Coalescent Model, GMYC). Both approaches unambiguously recognized E. (C.) turcicus sp. nov. as a distinct species. Our molecular dataset contains all Caucasiron species occurring in the Caucasus and the delimitation of individual species mostly follows the morphologically defined species. This study confirms the suitability of the GMYC approach for species delimitation within Caucasiron.
Keywords: taxonomy; mayflies; new species; Caucasus; barcoding